Upaya Peningkatkan Kemampuan Motorik Halus Anak melalui Kegiatan Mewarnai di Kelompok Bermain Cut Nya’ Dien Bojonegoro - Novi Dyah Ayu Putri; Eka Saptaning Pratiwi; Sriyanti (Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
This study aims to describe efforts to improve children's fine motor skills through coloring activities at the Cut Nya' Dien Playgroup in Bojonegoro. This study uses a qualitative case study approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that efforts to improve children's fine motor skills are carried out through nine steps, such as providing media, planning, implementation, individual and group approaches, fun methods, guidance, evaluation, and appreciation. Through this study, the researchers saw that using these 9 strategies is very effective in helping develop children's fine motor skills at the playgroup age level.